Prelom s starim in ustvarjanje nove elite - Petelin, David (Dileme, 2018)
The transformation of the economic and political system during or after the war is the biggest milestone in Slovenian contemporary history. The social and demographic structure changed. A new, revolutionary class seized power in the state. Trials were being organised by authorities across Yugoslavia as well as in Slovenia. The absolute victory of the Party in domestic politics, confrontation with the bourgeoisie, and social change brought transformation in the part of the Ljubljana social scheme that belonged to the highest class - the so-called elite. The bourgeoisie and its values were unwanted, set aside, and eventually eliminated. After the war, many members of the bourgeoisie were killed or imprisoned, many emigrated, others were disowned while some joined the Party and thus (sometimes unintentionally) betrayed the bourgeois tradition.
Keywords: 1945/1952; bourgeoisie; družbeni razredi; expropriation; meščanstvo; nacionalizacija; nationalisation; razlastitev; Slovenia; Slovenija; social classes; socialism; socializem